Benefits of Ayurveda Health Tourism: An Exploratory Study on Health Tourists Visiting South Kerala (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Ayurveda health tourism is emerging as a niche  segment in the tourism landscape across the  world. Ayurveda wellness therapies provide  holistic and long-lasting health benefits to  health and wellness seekers. The preventive,  curative, relief and rehabilitative nature of  ayurveda coupled with culture, tradition and  local services provide various tangible and  intangible benefits to tourists who demand such  tourism services from ayurveda health Centres.  Ayurveda is practised in its purest form in  the Indian state of Kerala which inherited the  traditional ‘Vaidya’ system of ayurveda, scenic  beauty, the blend of tourist attractions and rich  cultural heritage. The ayurveda health Centres  in Kerala are emerging as the hub of wellness  Centres with global access and brand image.  The paper looks into various types of benefits  received by Ayurveda health tourists visiting  ayurveda Centres in southern Kerala. Data  was collected from 500 health tourists using a  structured interview schedule on 28 tourism  attributes using 5 point Likert scale during the  period September to April 2019. The important  factors influencing the benefits of wellness  tourists are identified through explorative factor  analysis. Health outcome, Uniqueness, Novelty,  Mental well-being and Physical appearance are  the benefit factors identified in this study. The  benefits identified in the study are important in  designing customized services and expanding the  health tourism market in Kerala.
Keywords: Ayurveda; Health Tourism; Tourism Benefits; Kerala Tourism